Study of the Correlation Between Multiple Chemical Sensitivity and Personality Using the Quick Environmental Exposure Sensitivity Inventory Questionnaire and the Temperament and Character Inventory. Issue 7 (July 2020) - Lu, Xi; Hisada, Aya; Anai, Akane; Nakashita, Chihiro; Masuda, Shota; Fujiwara, Yuki; Kunugita, Naoki; Katoh, Takahiko
N/A: Objective: We conducted an analysis using the Quick Environmental Exposure Sensitivity Inventory to examine the correlation between multiple chemical sensitivity (MCS) and personality traits by using temperament and character inventory, and environmental exposures. Methods: An anonymous questionnaire was distributed to 667 employees working at an IT manufacturing plant in Japan. Variables including chemically sensitive population (CSP), personality, and environmental chemical exposure were individually evaluated using U -test, chi-squared test, and correlation analyses. We also did covariance structure analysis to build a structural equation model. Results: There was little direct impact of temperament on the CSP, while there was a significant impact of character on the CSP. Women were more likely to exhibit symptoms of CSP. Conclusion: MCS is correlated with personality, impacted more by character acquired later in life than innate temperament. There were sex differences in the incidence of MCS.